Elaboración de recursos didácticos con material reciclable para desarrollar conciencia léxica, fonológica y semántica del niño y niña del centro educativo Luis Burbano Mancheno del primero de básica paralelo “B” ubicado en la parroquia La Matriz del cantón Latacunga de la provincia de Cotopaxi durante el año 2010 – 2011 - Vega Guanochanga, Mónica Aracely (2015)
This research contribution was based on the development importance of learning resources within the learning process with it classroom application achieving an integral children learning from an early age, and these were prepared from reusable resources to develop the lexical, semantic and phonological awareness, searching for an optimal nursery language. This research was performed in the children's center "Luis Burbano Mancheno" After considering the little knowledge of techniques and alternatives to develop educational resources for teaching and learning process that contributes to kids development, by parents and teachers, application of workshops making it necessary to socialize the themes and activities. For different methodologies development; were applied and observed on babies who had a lack knowledge about these waste materials so that it may be useful to benefit them, because it was based on the theoretical and practical designed with information obtained from several specialized authors on the subject central base to the planning of activities in the educational process within this institution, the same as the planned activities culminate expressed their pleasure at all imparted knowledge and commitment to be in constant preparation according to the progress that modern world demands and offers.